Disentangling the ISM phases of the dwarf galaxy NGC 4214 using [C II] SOFIA/GREAT observations - Fahrion, Katja; Cormier, Diane; Bigiel, Frank; Hony, Sacha (Astronomy and astrophysics, 2017)
The [C ii] 158 μm fine structure line is one of the dominant cooling lines in the interstellar medium (ISM) and is an important tracer of star formation. Recent velocity-resolved studies with Herschel/HIFI and SOFIA/GREAT showed that the [C ii] line can constrain the properties of the ISM phases in star-forming regions. The [C ii] line as a tracer of star formation is particularly important in low-metallicity environments where CO emission is weak because of the presence of large amounts of CO-dark gas.Aims. The nearby irregular dwarf galaxy NGC 4214 offers an excellent opportunity to study an actively star-forming ISM at low metallicity. We analyzed the spectrally resolved [C ii] line profiles in three distinct regions at different evolutionary stages of NGC 4214 with respect to ancillary H i and CO data in order to study the origin of the [C ii] line.Methods. We used SOFIA/GREAT [C ii] 158 μm observations, H i data from THINGS, and CO(2 → 1) data from HERACLES to decompose the spectrally resolved [C ii] line profiles into components associated with neutral atomic and molecular gas. We use this decomposition to infer gas masses traced by [C ii] under different ISM conditions.Results. Averaged over all regions, we associate about 46% of the [C ii] emission with the H i emission. However, we can assign only ~9% of the total [C ii] emission to the cold neutral medium (CNM). We found that about 79% of the total molecular hydrogen mass is not traced by CO emission.Conclusions. On average, the fraction of CO-dark gas dominates the molecular gas mass budget. The fraction seems to depend on the evolutionary stage of the regions: it is highest in the region covering a super star cluster in NGC 4214, while it is lower in a more compact, more metal-rich region.
Gesehen am 25.10.2017